2020
DOI: 10.3329/bjar.v44i4.45698
|View full text |Cite
|
Sign up to set email alerts
|

Moisture level and storage container effects on seed quality of soybean genotypes under ambient condition

Abstract: The experiment was conducted at the Seed Laboratory, Regional Agricultural Research Station, Bangladesh Agricultural Research Institute, Jamalpur in 2013 to study the effect of seed moisture content and storage containers on seed quality of soybean genotypes. Three genotypes of soybean (AGS 191, ASET 93 and Shohag), four initial seed moisture content (6, 8, 10 and 12%) and two types of storage containers (polythene bag and glass jar) were included in the experimental treatment. Seeds of soybean genotypes was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…The LPA, RARP, RALP, and MRAPP presented the higher percentage variation of germination after 6 months. Some authors verified in soybean seeds stored under uncontrolled humidity and temperature conditions an increase in moisture content at 45 and 180 days (André et al, 2022); however, moisture content fluctuation occurred between 90 and 135 days due to the variation in relative humidity of the air, which favored the sorption processes of the seeds (Ali et al, 2020;Coradi et al, 2022). Evaluating different seed packaging materials for quality of rice seed stored at different periods of time, Assaye et al (2023) found high germination, seedling length, seedling dry weight, and vigor indices due to the low variation in the water content of seeds over storage time, similar to the results obtained with LPA, RARP, RALP, and MRAPP packaging.…”
Section: Resultsmentioning
confidence: 99%
“…The LPA, RARP, RALP, and MRAPP presented the higher percentage variation of germination after 6 months. Some authors verified in soybean seeds stored under uncontrolled humidity and temperature conditions an increase in moisture content at 45 and 180 days (André et al, 2022); however, moisture content fluctuation occurred between 90 and 135 days due to the variation in relative humidity of the air, which favored the sorption processes of the seeds (Ali et al, 2020;Coradi et al, 2022). Evaluating different seed packaging materials for quality of rice seed stored at different periods of time, Assaye et al (2023) found high germination, seedling length, seedling dry weight, and vigor indices due to the low variation in the water content of seeds over storage time, similar to the results obtained with LPA, RARP, RALP, and MRAPP packaging.…”
Section: Resultsmentioning
confidence: 99%